Wednesday Addams Antisocial Personality Disorder in Wednesday Netfilx Series - Amelia, Marla; Moelier, Dahlia D.; Rijal, Tabhan Syamsu (Fakultas Sastra, Universitas Bosowa, 2024)
This research examined antisocial personality disorder (ASPD) in Wednesday Addams, as portrayed in the movie script Wednesday by Alfred Gough and Miles Millar. Utilizing Theodore Millon's personality disorder theory and a qualitative descriptive analysis approach, the study aimed to identify ASPD criteria and its causes. The analysis revealed that Wednesday exhibited several traits associated with ASPD, including a lack of remorse, aggressive behavior, and a disregard for social norms. The study identified 33 examples of personality disorders, categorized into antisocial (15), passive-aggressive (10), histrionic (4), and sadistic (4). The research revealed that Wednesday's behavior was influenced by two main factors: traumatic events in childhood that fostered defensive and antagonistic attitudes, and parenting that encouraged outspoken expression without considering its emotional impact. These influences contributed to her disregard for social norms, lack of empathy, and difficulty in forming meaningful relationships.